Ask me anything: Martin Weides. (1st August 2022) - Tesh, Sarah
Abstract : Martin Weides is head of the quantum-circuits group at the University of Glasgow, UK, developing superconductor-based quantum circuits, including the cryogenic hardware, nanoelectronics chips and electronics needed for quantum computers. Weides is also consultant technical director to the UK-based firm Oxford Instruments Nanoscience.